2022
DOI: 10.1097/bpo.0000000000002197
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lower Extremity Rotational Malalignment on Pediatric Patient-reported Outcomes Measurement and Information System (PROMIS) Scores

Abstract: Background: There is sparse literature demonstrating the relationship between lower limb pediatric idiopathic rotational malalignment (IRM) and patient-reported outcomes measurement information system (PROMIS) scores. Our goal is to determine and quantify the amount that IRM deformities, as measured with the 3D gait analysis, affect childrens’ pain interference, mobility, and peer relationship PROMIS domains. Secondary outcomes include investigating the potential relationships between IRM and vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…MacWilliams et al showed correction of idiopathic TT normalized frontal plane knee moments and restored ankle power [8]. Other studies have demonstrated the detrimental effect on patient pain, function and mentality from malalignment [6,7]. The improvement in PODCI and GAS scores post-operatively from corrective osteotomy in this series echo the results of Stambough et al reporting improved IKDC-9 scores with femoral derotational osteotomy [39].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…MacWilliams et al showed correction of idiopathic TT normalized frontal plane knee moments and restored ankle power [8]. Other studies have demonstrated the detrimental effect on patient pain, function and mentality from malalignment [6,7]. The improvement in PODCI and GAS scores post-operatively from corrective osteotomy in this series echo the results of Stambough et al reporting improved IKDC-9 scores with femoral derotational osteotomy [39].…”
Section: Discussionsupporting
confidence: 72%
“…Associations of malrotation with patellofemoral pathology, anterior knee pain, abnormal gait, FAI, and potential predisposition for injury and osteoarthritis have all been reported [4,5]. More recently, the effect of these deformities on patient-reported outcomes has been highlighted, demonstrating lower PODCI and PROMIS scores [6,7]. Traditionally, and currently, at most centers, the clinical examination is the principal diagnostic tool available.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] A number of studies have validated select PROMIS domains against specific legacy measures in patients across a wide spectrum of upper and lower limb conditions, including idiopathic lower limb rotational malalignment, congenital anomalies, and posttraumatic amputations. [8][9][10][11] Furthermore, multiple comparisons of PROMIS and SRS scores have sought to validate the novel generic instrument against the legacy disease-specific measures in patients with spinal deformity, 6,[12][13][14][15][16][17][18][19] but none have yet to validate PROMIS against the LD-SRS for pediatric patients with lower limb differences. We sought to assess the concurrent validity of select Patient-reported Outcomes Measurement Information System (PROMIS) domains and Limb Deformity-Scoliosis Research Society (LD-SRS) scores in pediatric patients with lower limb differences.…”
mentioning
confidence: 99%
“…As a generic HRQoL measure, PROMIS confers a number of benefits—including reduced administrative burden, faster time to completion, and diminished floor and ceiling effects when compared with legacy measures—to researchers, clinicians, and patients alike 5–7 . A number of studies have validated select PROMIS domains against specific legacy measures in patients across a wide spectrum of upper and lower limb conditions, including idiopathic lower limb rotational malalignment, congenital anomalies, and posttraumatic amputations 8–11 …”
mentioning
confidence: 99%